Are the concerns destroying mental health of college students?: A qualitative analysis portraying experiences amidst COVID‐19 ambiguities. Issue 1 (1st February 2021) - Gupta, Riya; Agrawal, Rachna
Abstract: Coronavirus presenting an unforeseeable chain of events has exaggerated misery for students in India as they attracted the most detrimental experiences associated with lockdown restrictions leading to a shutdown of colleges as a preventive measure. The research endeavors to furnish a review of the overall hardships and psychological state of mind of college students and improvement in the implementation of policy decisions. Researchers conceptualize the newly discovered phenomenon by adopting grounded theory. Data from 256 newspaper articles, online articles and magazines have been gathered and converted into 256 separate files. To broaden the justification of research, social media analysis employing tweets, Facebook posts and Whatsapp messages are considered adding to the contributory prospects of the study. Compiled data is then refined through data mining technique. Triangulation approach amalgamating content analysis and thematic analysis has been deployed, thereby exploring the qualitative aspect of data gathering. Reviews from 31 students through telephonic conversation and 8 academic experts extended more accuracy to the research process. Findings administered academic disruptions with career concern, emotional suffering, financial concern, online learning, overseas injustice and psychological effects as the final themes representing various concerns experienced by college students. Hence, this work concludes with some constructive suggestions to deteriorate the amplified concerns.